The effects of genetic variation and environmental factors on rhynchophylline and isorhynchophylline in Uncaria macrophylla Wall. from different populations in China. - Mei-Fang Song; Yan-Hong Guan; Hai-Tao Li; Shu-Gen Wei; Li-Xia Zhang; Zhong-Lian Zhang; Xiao-Jun Ma (PLoS ONE)
Uncaria macrophylla Wall. is an important Chinese medicinal herb. Rhynchophylline (RIN) and isorhynchophylline (IRN) are its major active compounds. We investigated the influence of genetic differentiation and environmental factors on the RIN and IRN to find the main influencing factors of their contents and lay the foundation for the following cultivation and breeding. We used inter-simple sequence repeat (ISSR) markers to investigate the genetic diversity, and high-performance liquid chromatography (HPLC) to measure the contents of RIN and IRN in 200 samples of U. macrophylla obtained from nine natural populations, and then to analyze the correlation between genetic differentiation, environmental factors of sampling sites and the contents of RIN and IRN. We found that High intra-population (80.05%) and low inter-population (19.95%) genetic diversity existed in the samples of U. macrophylla. To some extent, genetic differentiation and the contents of RIN and IRN had correlation in individual populations (such as JH, MH, XM, and ML). The RIN and IRN contents were significant negatively correlated with the precipitation in May (RIRN = -0.771, p = 0.015) and June (RRIN = -0.814, p = 0.008; RIRN = -0.921, p = 0.000), indicating that precipitation was the main affecting factor of their contents. Interestingly, the analysis results showed that the RIN content had a significant positive correlation (r = 0.585, p = 0.000) with the IRN content (they are isomers); the proportion of RIN had a significant negative correlation with the sum of the two (r = -0.390, p<0.0001), while the proportion of IRN had a significant positive correlation (r = 0.390, p<0.0001). It meant that, with the total quantity of the two compounds increased, the proportion of RIN decreased and the proportion of IRN increased, illustrating that their conversion exist some regularity. Moreover, the content ratio of RIN and IRN was significant positively correlated with the January precipitation (r = 0.716, p = 0.030), implying that January may be the key period for the mutual transformation of RIN and IRN.